PERAN KEGIATAN EKSTRAKURIKULER RISTA DALAM MENUMBUHKAN SIKAP NASIONALISME PADA PESERTA DIDIK. - Zulkifli, Zulkifli (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
This study examines the role of the Rista extracurricular program at MA Attaufiqiyah in fostering students' nationalism. Although focused on Islamic religious values, Rista also instills nationalism through activities such as national discussions, fundraising, and social service projects. These activities not only strengthen students' moral and spiritual foundation but also foster patriotism, unity, tolerance, and social responsibility. Using a qualitative approach with descriptive methods, data were collected through observation, interviews, and documentation. The results show that Rista effectively integrates nationalism with Islamic teachings, allowing students to understand and practice nationalism. The integration of Rista with Civic Education (PPKn) provides a holistic approach to shaping students' nationalist character by combining religious and national values. These findings emphasize the importance of educational strategies that merge religious and national values to shape a young generation that cherishes both their faith and their nation.